Homemaking away from home: a semiotic cultural psychology perspective - Märtsin, Mariann (Frontiers in Psychology, 2023)
How do migrants create a sense of home in the context of migration? What does it mean for a person to physically move away from one home and psychologically move towards another one somewhere else? How do migrants create a sense of continuity between the home that is no longer there and the home that is not yet here? This theoretical paper is an invitation to address these questions from a semiotic cultural psychology perspective. The paper emphasizes the importance of both geographical and semiotic movements in understanding the migration process. It shifts the focus away from tangible aspects of migration and towards the imagined and desired aspects in the process of homemaking. The concept of home is explored as a semiotic construction that guides human meaning-making processes, emphasizing its affective value and highlighting the dynamic dialectics of home and non-home. This alternative conceptualization offers new ways of understanding homemaking and being at home, beyond the commonly celebrated ideals of being settled or always on the move. Finally, the paper discusses the dynamic and developmental nature of migration, which can both threaten and open up opportunities for transformation and development, and suggests some general methodological principles that could guide research about the interplay between homemaking, migration and culture.